2015
DOI: 10.4028/www.scientific.net/ssp.242.236
|View full text |Cite
|
Sign up to set email alerts
|

Internal Gettering of Copper for Microelectronic Applications

Abstract: The results of this work have shown that for microelectronic applications, gettering at dislocations is less important and oxygen precipitates are the main getter sink for Cu. Sufficient gettering of Cu in samples contaminated with low Cu concentration requires a higher density and larger oxygen precipitates compared to samples contaminated with high Cu concentration. It is demonstrated that the getter efficiency depends on the contamination level of the samples and getter test with low contamination level mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…37 It is very unlikely that this is based on nucleation of copper silicide precipitates because of the low temperature and the low supersaturation. Segregation effects become more pronounced with decreasing temperature and segregation gettering would still work.…”
Section: Discussionmentioning
confidence: 99%
“…37 It is very unlikely that this is based on nucleation of copper silicide precipitates because of the low temperature and the low supersaturation. Segregation effects become more pronounced with decreasing temperature and segregation gettering would still work.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] It was also demonstrated that metallic impurities can be effectively trapped at oxygen precipitates in the process of gettering. [5][6][7][8][9] All these features of the oxygen precipitates require the control of precipitation in the production process of silicon devices. However, this cannot be optimally executed if the features of oxygen precipitates like their composition are not fully known.…”
mentioning
confidence: 99%
“…A concentration‐dependent gettering efficiency was already observed for other transition metals such as copper. [ 14 ]…”
Section: Resultsmentioning
confidence: 99%
“…A concentration-dependent gettering efficiency was already observed for other transition metals such as copper. [14] Table 1. Backside layers and resistivity of the specimens.…”
Section: Resultsmentioning
confidence: 99%